2022
DOI: 10.1186/s12931-022-02080-z
|View full text |Cite|
|
Sign up to set email alerts
|

Reference values of impulse oscillometry (IOS) for healthy Chinese children aged 4–17 years

Abstract: Objective To establish the predicted value of pulmonary function determined by impulse oscillometry (IOS) in children (4–17 years old) in China. Methods A total of 6270 healthy children aged 4–17 years in China were included. The Master Screen IOS pulmonary function device (Jaeger Co, Germany) was used to detect the respiratory impedance (Zrs), resonant frequency (Fres), respiratory system resistance (Rrs) and respiratory system reactance (Xrs) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…The acceptability and success rate of lung function measured using oscillometry technique in a populationbased cohort of 3-year-old children were good and comparable to previous studies [21], thus confirming that oscillometry is easily performed in pre-school children. In accordance with previous population-based studies [14,25,30], height was observed as an important determinants of respiratory impedance. Mean Zscore values for R 7 and X 7 observed in our population were 0.5 indicating slightly higher values as compared to the population used as reference in Shackleton et al [25].…”
Section: Discussionsupporting
confidence: 91%
“…The acceptability and success rate of lung function measured using oscillometry technique in a populationbased cohort of 3-year-old children were good and comparable to previous studies [21], thus confirming that oscillometry is easily performed in pre-school children. In accordance with previous population-based studies [14,25,30], height was observed as an important determinants of respiratory impedance. Mean Zscore values for R 7 and X 7 observed in our population were 0.5 indicating slightly higher values as compared to the population used as reference in Shackleton et al [25].…”
Section: Discussionsupporting
confidence: 91%
“…17 IOS may be a potential screening tool for OSA diagnosis as it can detect upper airways stenosis or patency in OSA. 18 However, the relationship between lung function and OSAHS, especially in obese patients, is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified that the article note about equal contribution was missing.…”
mentioning
confidence: 99%